Environmental and Economic Assessment of Leak and Loss Audits at Natural Gas Compressor and Storage Facilities. Issue 12 (27th November 2014) - Johnson, Derek; Covington, April; Clark, Nigel; Veser, Götz
Abstract According to the United States (US) Energy Information Administration (EIA), the annual US natural gas consumption is forecast to grow from 25.6 trillion cubic feet (TCF) in 2012 to 31.6 TCF in 2040 (1 CF≈28.3 L). The main component of natural gas is methane, a potent greenhouse gas (GHG). As the natural gas supply chain grows, there is increased scrutiny over leaks and losses that occur during the multiple stages from development to end users. West Virginia University′s (WVU) Center for Alternative Fuels, Engines, and Emissions conducted leak and loss audits at five natural gas compressor and storage facilities in the Barnett Shale region of Texas. We have reported elsewhere on the site‐specific total leak and loss rates.11–13 This article provides an environmental and economic assessment of the total methane (natural gas) losses at these facilities. Other studies report the methane emissions in terms of tons per year, whereas this paper examines the environmental impact of these emissions through an equivalent CO2 emissions rate using multiple global warming potentials. This paper also examines the lost revenue from these leaks and the overall social cost of carbon (SCC) that could be assessed to these facilities under a proposed carbon tax. The methane leaks and losses from these sites result in CO2 equivalent emissions of over 70 000 and 24 000 metric tons annually, using a 20‐year and 100‐year global warming potentials (GWPs), respectively. Using a SCC of $ 37 per metric ton, this would result in annual costs of $ 2.6 million and $ 915 000 for these sites based on the respective GWPs.